2021
DOI: 10.21203/rs.3.rs-415584/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gender Differences in Psychosocial Status of Adolescents During COVID-19: A Six-country Cross-sectional Survey in Asia Pacific

Abstract: Background: School closures and family economic instability caused by the COVID-19 lockdown measures have threatened the mental health and academic progress of adolescents. Through secondary data analysis of World Vision Asia Pacific Region’s COVID-19 response-assessments in May-June 2020, this study examined whether adolescents’ study, physical, and leisure activities, psychosocial status, and sources of COVID-19 information differed by gender. Methods: The assessments used cross-sectional surveys of adolesce… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…The fact that respondents who assessed their health as bad had worse depression and anxiety change could possibly be a sign of health anxiety among students in Georgia (Kibbey et al, 2021). The study highlights one more population where the pandemic has affected females’ mental health significantly more than males’ (Prowse et al, 2021; J. Wang et al, 2021).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The fact that respondents who assessed their health as bad had worse depression and anxiety change could possibly be a sign of health anxiety among students in Georgia (Kibbey et al, 2021). The study highlights one more population where the pandemic has affected females’ mental health significantly more than males’ (Prowse et al, 2021; J. Wang et al, 2021).…”
Section: Discussionmentioning
confidence: 94%
“…(Brooks et al, 2020; Romeo et al, 2021). Females and international students have been suggested to be particularly vulnerable, though evidence of this is not consistent (Alam et al, 2021; Chen et al, 2020; Gestsdottir et al, 2021; Kim & Kim, 2021; Pappa et al, 2020; Prowse et al, 2021; J. Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Recent analysis from six countries in the Asian Pacific region showed that adolescent girls were more likely to feel isolated or stressed, be concerned about education and household income. [39] High levels of psychological distress have been reported during the COVID-19 pandemic among adolescents in different parts of India. [17,31,32,[40][41][42] A study among adolescent girls from six states reported concerns related to selfisolation, worries about academics, physical health and safety, as well as global and societal concerns.…”
Section: Discussionmentioning
confidence: 99%
“…Our study revealed that psychological stress, anxiety, and depression were the most common health problems among high school seniors during the pandemic. Adolescent girls are 1.13 times more likely to feel stressed than boys (J. Wang et al, 2021). Likewise, with depression and anxiety, girls compared to boys experienced more depression and anxiety with a ratio of 50.7% versus 30.7% and 46.9% compared to 26.7%, respectively (AlAzzam et al, 2021).…”
Section: Discussionmentioning
confidence: 99%